What impact has the United Kingdom Clinical Aptitude Test (UKCAT) had on selection to undergraduate medicine and dentistry in the UK? - Greatrix, Rachel (2022)
The United Kingdom Clinical Aptitude Test (UKCAT) Consortium was established in 2005 with the aims of achieving greater fairness in selection to medicine and dentistry, widening participation in medical and dental training and improving the evidence base around selection in the UK. The UKCAT was first used in selection in 2006.